Business intelligence bajo plataforma IP versión 6 y su influencia en la gestión empresarial - Hayashida Marchinares, Augusto Enrique (2009)
-- The advent of Internet, the phone mobile and the globalization have modified the forms of communication in the world and the enterprises in general. All this has brought the search of facilities of communications permanents, mobilities and secures with quality of service to improve the Internet and the new aplications on devices mobile. The studies of the new protocol of internet as Ipv6 are in a proces that consist in finding new focus to improve the quality of service. This thesis consists in analyzing and give recomendations of Ipv6 with Business Intelligence to demonstrate that the use improve the management in the enterprises. Ipv6 is the best solution to improve the throughput in the network. The other side, it proposes a new way of business on internet y the born the new aplications as for example the m-commerce and Business Intelligence since any devices mobile.